Neuroligins and Neurodevelopmental Disorders: X-Linked Genetics - Nguyen, Thien A.; Lehr, Alexander W.; Roche, Katherine W. (Frontiers in Synaptic Neuroscience, 2020)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder that results in social-communication impairments, as well as restricted and repetitive behaviors. Moreover, ASD is more prevalent in males, with a male to female ratio of 4 to 1. Although the underlying etiology of ASD is generally unknown, recent advancements in genome sequencing have facilitated the identification of a host of associated genes. Among these, synaptic proteins such as cell adhesion molecules have been strongly linked with ASD. Interestingly, many large genome sequencing studies exclude sex chromosomes, which leads to a shift in focus toward autosomal genes as targets for ASD research. However, there are many genes on the X chromosome that encode synaptic proteins, including strong candidate genes. Here, we review findings regarding two members of the neuroligin (NLGN) family of postsynaptic adhesion molecules. Neuroligins have multiple isoforms and are both autosomal and sex-linked. The sex-linked genes, NLGN3 and NLGN4, are both on the X chromosome and were among the first few genes to be linked with ASD and intellectual disability (ID). In addition, there is a less studied human neuroligin on the Y chromosome, NLGN4Y, which forms an X-Y pair with NLGN4X. We will discuss recent findings of these neuroligin isoforms regarding function at the synapse in both rodent models and human-derived differentiated neurons, and highlight the exciting challenges moving forward to a better understanding of ASD/ID.